STRATEGI MANAJEMEN TALENTA UNTUK MENINGKATKAN RETENSI KARYAWAN GENERASI MILENIAL DAN Z - Yetti Kuniawaty; Teguh Iman Santoso; Titin Supini; Munawaroh Munawaroh (LPPM Politeknik Pratama, 2025)
Talent management strategies have become a key focus for organizations in facing employee retention challenges, especially in millennials and Gen Z who have unique characteristics and different work needs compared to previous generations. This study aims to explore effective talent management strategies to increase employee retention in the two generations through a literature review approach. Data is taken from various academic studies, industry reports, and relevant journal articles in the last 10 years. The results of the study show that strategies that emphasize work flexibility, structured career development, inclusive organizational culture, and the use of digital technology in human resource management have a significant influence on employee retention. In addition, employee involvement in strategic decision-making is also a key factor in increasing the loyalty of millennials and Generation Z. This research providesKeywords: enterprise resource planning, supply chain management, system implementation, company performance improvement, systematic literature review.